Gelatin Used as a Transductor in an Optical Hygrometer Based on a Fabry-Perot Interferometer - Sergio Calixto (Advances in Materials Science and Engineering)
The quantities that are usually measured are time, pressure, temperature, and relative humidity to mention but a few. The word humidity is used when we are dealing with water vapor which is a gas. The instrument used to measure the humidity is the hygrometer that can be based on electronics, optics, mechanics, chemicals, and others. The measurement of humidity shows its importance in applications such as food processing, meteorological, semiconductor, building and construction, medical, and automotive to mention but a few. This paper shows the adaptation of an optical interferometer, the Fabry-Perot (F-P), to measure the relative humidity. The transductors that have been probed are gelatin-thin films that are inserted between the mirrors of the FP. When water molecules are absorbed (desorbed) by the gelatin film, its refractive index and thickness change giving a movement of the rings in the interference pattern. The calibration plot comprises the ring displacement as a function of the relative humidity.